Shifting interior spaces a study on continuous occupancy among selected resident families in a government housing development - Amador, Andrea Ruiza N. (College of Home Economics, University of the Philippines Diliman, 2018)
Abstract. This study sought to find out how residents of selected NHA employee housing units utilized and manage their once generic domestic interior spaces and subsequent layers of the home within at least thirty years of occupancy since 1982. Three identical houses in an NHA employee housing development were purposively selected as the locale of the immersive research. Data was gathered using the multiple embedded case study approach were direct observation , structured open -ended interview and cognitive mapping were administrative with two respondents of each sample house. The data was organized to recreate the different lives of the home chronologically, which was then validated with the respondents. In the analysis using a Post-Occupance Evaluation that is patterned after Vitruvius' ideals of good architecture app;ied to interior design it was affirmed that physical, cultural and behavioral connection of residents with their interior space was the stimuli that make buildings learn and adopt over time. Cross-case analysis was made after the examination and quantification of all three samples. One of the most significant findings is that the Space plan governs the other subsequent layers of change. All sample houses studied grew in usable floor area from 200.56% to 538.44% - but the frequency and intensity of changes are not proportional to the total number of residents. Future studies of the same nature are encouragged to be conducted with the different demographic to gain external validation. Although it was observed that shell houses are flexible enough for resident capacitiers and preferences to be accomodated to be accomodated, it would have been better if certain measures were enforced by the professionals involved in the design of the home. There needs to be a shift in the way design professionals see how their buildings perform over time. Allowing adaptibility to be ingrained in the design of domestic spaces allow life to be better accomodated in the places designed to be lived in by others.